1996
DOI: 10.1104/pp.111.4.1051
|View full text |Cite
|
Sign up to set email alerts
|

Central Roles for Potassium and Sucrose in Guard-Cell Osmoregulation

Abstract: Osmoregulation in guard cells of intact, attached Vicia faba leaves grown under growth chamber and greenhouse conditions was studied over a daily light cycle of stomatal movements. Under both growth conditions guard cells had two distinct osmoregulatory phases. In the first (morning) phase, opening was correlated with K+ uptake and, to a lesser extent, sucrose accumulation. In the second (afternoon) phase, in which apertures were maximal, K+ content declined and sucrose became the dominant osmoticum. Reopening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
0
8

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(142 citation statements)
references
References 12 publications
8
119
0
8
Order By: Relevance
“…Our results for Experiment I (a rapid increase in K +, followed by a decline even as stomata remained open) are reminiscent of those reported by Talbott et al [21], whereas those of Experiment II (a less rapid increase in K ÷, which trailed the aperture-size increase) are reminiscent of those of Laffray et al [10]. The important role of K ÷ in stomatal movements [24] is unquestioned, but its role as the sole osmolyte that effects stomatal movements deserves reevaluation.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our results for Experiment I (a rapid increase in K +, followed by a decline even as stomata remained open) are reminiscent of those reported by Talbott et al [21], whereas those of Experiment II (a less rapid increase in K ÷, which trailed the aperture-size increase) are reminiscent of those of Laffray et al [10]. The important role of K ÷ in stomatal movements [24] is unquestioned, but its role as the sole osmolyte that effects stomatal movements deserves reevaluation.…”
Section: Discussionsupporting
confidence: 78%
“…Intrigued by the reports that guard-cell potassium content declines over the diel cycle [20,21] and that changes in guardcell potassium content are not coordinated always with changes in stomatal aperture [8 11], we assayed semiquantitatively for K and CI in guard cells of growth-chamber-grown plants. Taken together, our semiquantitative elemental analyses revealed K and C1 fluctuations but the analyses did not show a reproducible correlation between the amounts of these elements and sucrose (or stomatal apertures).…”
Section: Symplastic Potassium and Chloride Contents Of Guard Cells Ovmentioning
confidence: 99%
“…Em contrapartida, o tratamento T5 apresentou os melhores resultados, no qual os valores de diâmetro e altura das mudas dispersaram em 1,5 e 7,0 mm, respectivamente, em relação à mediana. processo de fotossíntese, respiração e síntese de proteínas, atuando também na abertura estomática, no transporte via floema, na osmorregulação e na extensão celular (HuBeR, 1985;MaRSCHNeR, 1995;lavON e gOlDSHMiDt, 1999;talBOtt et al, 1999).…”
Section: Resultsunclassified
“…Salt is known to reduce K uptake (Cramer et al, 1987). Low K levels can reduce photosynthetic performance (Chow et al, 1990) and stomatal control of water loss (Talbott & Zeiger, 1996). Several Danish and Swedish authors including Saxe (1993) suggested that tropospheric ozone could also be a contributing factor in the recent outbreak of the ' top dying ' syndrome.…”
Section: mentioning
confidence: 99%